An enigmatic case of cortical anopsia: Antemortem diagnosis of a 14-3-3 negative Heidenhain-variant MM1-sCJD. Issue 1 (1st January 2020) - Obergassel, Julius; Lohmann, Lisa; Meuth, Sven G.; Wiendl, Heinz; Grauer, Oliver; Nelke, Christopher
ABSTRACT: Sporadic Creutzfeldt-Jakob disease is the predominant type of human prion disease. While routine diagnostic in phenotypic cases has advanced considerably, the clinical heterogeneity and rarity of subtypes continue to constitute a major clinical and diagnostic challenge. Here, we report a peculiar case of the Heidenhain-variant of MM1 sporadic Creutzfeldt-Jakob disease presenting as a stroke mimic in an 81-year-old patient with a rapid and clinically distinct course of disease as compared to previously reported cases. While 14-3-3 protein was negative, clinical findings substantiated by 18 F -FDG-PET imaging and RT-QuIC-Assay were able to establish the diagnosis. We conclude that in cases presenting with rapid progressive dementia secondary to sudden cortical anopsia the Heidenhain-variant of CJD should be considered.